2004
DOI: 10.1016/j.jtherbio.2004.08.081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of individual characteristics on a mathematical model of human thermoregulation

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…This suggests that UTCI allows for adequate comparisons of climatic conditions and again confirms the simplified approach taken by UTCI to develop an assessment scale based on responses to reference conditions. Interestingly, the inclusion of individually recorded clothing insulation as additional input to the UTCI-Fiala model even impaired the predictive capacity, although individualised models performed better in other contexts (van Marken Lichtenbelt et al 2004;Havenith and Middendorp 1990). One reason might be that differences in the choice of clothing insulation under identical climate conditions, which are evident by the large interindividual variation observed in this study sample, could partly reflect differences in individual thermoregulatory systems.…”
Section: Discussionmentioning
confidence: 81%
“…This suggests that UTCI allows for adequate comparisons of climatic conditions and again confirms the simplified approach taken by UTCI to develop an assessment scale based on responses to reference conditions. Interestingly, the inclusion of individually recorded clothing insulation as additional input to the UTCI-Fiala model even impaired the predictive capacity, although individualised models performed better in other contexts (van Marken Lichtenbelt et al 2004;Havenith and Middendorp 1990). One reason might be that differences in the choice of clothing insulation under identical climate conditions, which are evident by the large interindividual variation observed in this study sample, could partly reflect differences in individual thermoregulatory systems.…”
Section: Discussionmentioning
confidence: 81%
“…Local autonomic regulation was employed to modify local sweat rates, local blood flows, and tissue metabolic rates [21]. Former studies indicated that major physiological difference between ethnicity and individuals lies in the passive system [11,22]. A standard Chinese model was established based on the Fiala model with modifications in body size and composition.…”
Section: Standard Chinese Modelmentioning
confidence: 99%
“…Body fat was calculated through the measurement of skinfold caliper, which needs the measurement of circumference at levels of umbilicus, minimal abdominal width at approximately midway between xiphoid and umbilicus. Metabolic rate (MR) and body composition (BC) were selected as input parameters for the Fiala model individualization [11]. MR was calculated from the O 2 consumption and CO 2 production measured by indirect calorimetry, using a ventilated hood system, and the model achieved the best accuracy with the input of MR and BC.…”
Section: Input Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study employed a multi-segment method using four segments (Table 2) with respect to location of skin thermocouples and accounting for covered or bare body parts. This new method is in accordance with thermal energy budget models by Stolwijk and Hardy (1966), Fiala et al (2001), Huizenga et al (2001), van Marken Lichtenbelt et al (2004), and Munir et al (2009). Each body segment was assumed to possess a distinct T sk , r c , and aerodynamic resistance (r a ) to estimate convective heat exchange (C).…”
Section: Skin Temperaturementioning
confidence: 99%